HUBUNGAN BREASTFEEDING SELF EFFICACY DAN DUKUNGAN KELUARGA DENGAN KEBERHASILAN ASI EKSKLUSIF - Viqy Lestaluhu (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Mother's milk (ASI) is the best food and the only food a baby needs for the first six months. Breast milk is very necessary for the growth and development of children's intelligence. Many factors influence breastfeeding including knowledge, socio-economic cultural factors, physiological factors, family support, and educational factors from health workers. Psychological factors are also one of the problems that can affect milk production in postpartum mothers. Successful breastfeeding requires family support so that mothers are motivated to provide exclusive breastfeeding. In addition, the reason for the failure of successful exclusive breastfeeding is the condition of the mother, such as the mother's self-confidence or self-efficacy in breastfeeding. The purpose of this study is, the authors want to know the relationship between breastfeeding self-efficacy and family support with the success of exclusive breastfeeding. The type of research used is quantitative with a cross sectional design. The sample in this study was 30 breastfeeding mothers. Collecting data in this study used a questionnaire sheet containing questions about family support and the success of exclusive breastfeeding. Measuring tool to measure self-efficacy in breastfeeding mothers using the breastfeeding self-efficacy scale (BSES). The data obtained was then analyzed with the Chi Square test. The results of this study are, there is a significant relationship between Breastfeeding Self Efficacy and family support with the success of exclusive breastfeeding. Family support has a relationship with the success of exclusive breastfeeding for infants, this is supported by family knowledge about good breastfeeding. Breastfeeding mothers need to increase self-confidence and motivation in breastfeeding, increase knowledge about proper breastfeeding through counseling at health care facilitie.